Transcriptomic response of the picoalga Pelagomonas calceolata to nitrogen availability: new insights into cyanate lyase function - Nina Guérin; Chloé Seyman; Céline Orvain; Laurie Bertrand; Priscillia Gourvil; Ian Probert; Benoit Vacherie; Élodie Brun; Ghislaine Magdelenat; Karine Labadie; Patrick Wincker; Adrien Thurotte; et al. (Microbiology Spectrum)
ABSTRACT Cyanate (OCN−) is an organic nitrogen compound found in aquatic environments potentially involved in phytoplankton growth. Given the prevalence and activity of cyanate lyase genes in eukaryotic microalgae, cyanate has been suggested as an alternative source of nitrogen in the environment. However, the conditions under which cyanate lyase is expressed and the actual capacity of microalgae to assimilate cyanate remain largely underexplored. Here, we studied the nitrogen metabolism in the cosmopolitan open-ocean picoalga Pelagomonas calceolata (Pelagophyceae and Stramenopiles) in environmental metatranscriptomes and transcriptomes from culture experiments under different nitrogen sources and concentrations. We observed that cyanate lyase is upregulated in nitrate-poor oceanic regions, suggesting that cyanate is an important molecule contributing to the persistence of P. calceolata in oligotrophic environments. Non-axenic cultures of P. calceolata were capable of growing on various nitrogen sources, including nitrate, urea, and cyanate, but not ammonium. RNA sequencing of these cultures revealed that cyanate lyase was downregulated in the presence of cyanate, indicating that this gene is not involved in the catabolism of extracellular cyanate to ammonia. Based on environmental data sets and laboratory experiments, we propose that cyanate lyase is important in nitrate-poor environments to generate ammonia from cyanate produced by endogenous nitrogenous compound recycling rather than being used to metabolize imported extracellular cyanate as an alternative nitrogen source.IMPORTANCEVast oceanic regions are nutrient-poor, yet several microalgae thrive in these environments. While various acclimation strategies to these conditions have been discovered in a limited number of model microalgae, many important lineages remain understudied. Investigating nitrogen metabolism across different microalga lineages is crucial for understanding ecosystem functioning in low-nitrate areas, especially in the context of global ocean warming. This study describes the nitrogen metabolism of Pelagomonas calceolata, an abundant ochrophyte in temperate and tropical oceans. By utilizing both global scale in situ metatranscriptomes and laboratory-based transcriptomics, we uncover how P. calceolata adapts to low-nitrate conditions. Our findings reveal that P. calceolata can metabolize various nitrogenous compounds and relies on cyanate lyase to recycle endogenous nitrogen in low-nitrate conditions. This result paves the way for future investigations into the significance of cyanate metabolism within oceanic trophic webs.